'Te rua o te taniwha' : pākehā settlement of the Ruataniwha plains : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University, New Zealand - Gordon, Laurence James (Massey University, 2025)
Historians have generally characterised the Pākehā settlement of Hawke’s Bay as a socially stratified frontier where men of capital controlled both the rural and fledgling urban spaces. A space where owners of extensive pastoral runs taken up in the late 1850s and early 1860s dominated, both politically and socially. Development of rural communities and settlements has also been characterised as being male dominated, due to both the nature of the rural labour force and to the paternalistic hand of wealthy runholders. Based on a database of 769 individuals and utilising archival research, including contemporary newspapers and genealogical sources, this thesis investigates the ‘settler world’ on the Ruataniwha Plains. After the initial sale of land, Māori continued to engage with settlers and government seeking to advance the interests of hapū, fighting alongside government forces during the New Zealand Wars. Pākehā settling on the plains arrived with their own cultural and economic agenda and lived largely separate lives from their Māori neighbours. Government regionally and nationally, prioritised immigration and distributed land to cement control of the lower North Island. Farmers, labourers, businesspeople, men and women then established themselves and their families in an isolated rural environment. Initially, social supports were fragile, and some individuals fell through the cracks. In this context, families became the key social unit and are the research focus of this study. Family relationships could also be fragile. Relationship and health problems left women particularly vulnerable. Tracing the lives of women both within and outside the context of the family unit is a further focus of inquiry for this thesis. Community life on the plains was fluid, dynamic and complex. The ‘settler’ community allowed for an openness, particularly in relation to status, compared to the standard social pattern of the age, where relationships and conventions were more fixed. ‘Settler’ society was often profoundly unsettled, giving greater room for ‘ordinary’ immigrants to have an impact in community life that was larger than their status would imply. Community life was rich, varied and not always polite and comfortable. This study seeks to determine how ‘ordinary’ individuals and families found ways, within the dynamism of the local context, to build social links and develop community institutions.
Keywords: 430320 New Zealand history